Effect of Nano Silica and Coir Fiber on Compressive Strength and Abrasion Resistance of Concrete - Gupta, Mayank (My University, 2017)
Natural aggregate and cement are the basic elements of concrete. Due to exploding world population, construction activities are growing by leaps and bounds, leading to a whole new jungle of concrete, thus enhancing the requirement of the natural aggregate and cement. The production of the aggregates and cement is one of the major causes for environmental pollution. To set a balance between the environmental pollution and the cost of construction, search for other substitute material is the need of the hour, which can enhance the properties of concrete. This research is the investigation for examining the effect of nano silica and coir fiber on compressive strength and abrasion resistance of concrete. For completing the objective of the study, Coir fiber has been added in the concrete with the variation of 0.25 %, 0.5 %, and 0.75 % by the weight of the fine aggregates and 2 % and 3 % nano silica and 15 % fly ash have partially replaced cement inthe mix . Different samples with varying percentages of nano silica and coir fiber have been prepared keeping water to binder ratios as 0.47, 0.45 and 0.42 for calculating the compressive strength and abrasion resistance and results have been compared with the controlled specimens. After studying of the results, it is concluded that as the percentage of the Nano silica and Coir fiber is increasing, the compressive strength of the concrete increases up to the use of 0.5 % coir fiber and after that it drastically reduced. The improvement in the 7 days strength is more than the 28 days strength, thereby concluded that nano silica addition in concrete improves the early age strength. But as the percentage of the coir fiber is increased, the abrasion resistance of the concrete decreased thereby concluding that coir fiber may be not completely fill the present voids of the mix.
Master of Engineering -Structural Engineering
Keywords: Fly Ash; Nano Silica; Fly Ash; Compressive Strength; Abrasion Resistance